2017
DOI: 10.1146/annurev-clinpsy-021815-093459
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Mental Illness and Firearm Violence: Implications for Social Policy and Clinical Practice

Abstract: The United States has substantially higher levels of firearm violence than most other developed countries. Firearm violence is a significant and preventable public health crisis. Mental illness is a weak risk factor for violence despite popular misconceptions reflected in the media and policy. That said, mental health professionals play a critical role in assessing their patients for violence risk, counseling about firearm safety, and guiding the creation of rational and evidence-based public policy that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 111 publications
(125 reference statements)
2
40
0
Order By: Relevance
“…Here, we address actual policy initiatives designed to restrict access to firearms for people with mental illness. Given detailed reviews available elsewhere (e.g., McGinty et al., , Rozel & Mulvey, , Swanson et al., )—and the fact that the generalizability of this information to mass violence is unclear—we provide a targeted summary here.…”
Section: Synthesis Of Relevant Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we address actual policy initiatives designed to restrict access to firearms for people with mental illness. Given detailed reviews available elsewhere (e.g., McGinty et al., , Rozel & Mulvey, , Swanson et al., )—and the fact that the generalizability of this information to mass violence is unclear—we provide a targeted summary here.…”
Section: Synthesis Of Relevant Researchmentioning
confidence: 99%
“…First, background checks often fail to keep guns out of the hands of dangerous individuals who are prohibited from owning them. Although this is partly because of problems with implementing background checks, two other dynamics are at play: (a) Guns can be purchased without a background check from a private party, online, or at a gun show; and (b) guns are already in plentiful supply in U.S. households (see Rozel & Mulvey, ).…”
Section: Synthesis Of Relevant Researchmentioning
confidence: 99%
See 1 more Smart Citation
“… Easy access to guns. Numerous studies have shown that easy access to guns is a strong risk factor for violence (Chapman, Alpers, Agho, & Jones, ; Rozel & Mulvey, ; Siegel, Ross, & King, ). Research has also shown that stricter gun laws reduce gun‐related deaths around the world (Santaella‐Tenorio, Cerdá, Villaveces, & Galea, ).…”
Section: Environmental Risk Factors For Youth Violencementioning
confidence: 99%
“…It is also wrong. 1 Study after study shows that those who live with serious mental illness are far more likely to be the victims of violence rather than the perpetrators. 1 The narrative is, however, complicated because mental illness is associated with a statistically significant increase in violence, but accounts for only 4% of violent acts.…”
mentioning
confidence: 99%